1991
DOI: 10.1161/01.cir.83.3.995
|View full text |Cite
|
Sign up to set email alerts
|

Xanthine oxidase inhibition does not limit canine infarct size.

Abstract: BACKGROUND Evidence supporting the role of xanthine oxidase in myocardial reperfusion injury is based on studies with pharmacological interventions used to inhibit enzyme function. Controversy exists, however, regarding the true role of xanthine oxidase in reperfusion injury. This study was performed to determine whether xanthine oxidase inhibition limits myocardial injury due to coronary artery occlusion and reperfusion. METHODS AND RESULTS Anesthetize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
1

Year Published

1993
1993
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(10 citation statements)
references
References 58 publications
0
8
1
Order By: Relevance
“…Animal studies (27)(28)(29)(30) have shown both antinecrosis and antiarrhythmic effects with a host of pharmacological agents that modulate different intraand extracellular mechanisms. Indeed, Kingma et al (27,28), Denniss et al (29) and Werns et al (30) have documented significant reductions of infarct size in animal preparations of chronic coronary artery occlusion in the absence of restoration of blood flow.…”
Section: Myocardial Protectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Animal studies (27)(28)(29)(30) have shown both antinecrosis and antiarrhythmic effects with a host of pharmacological agents that modulate different intraand extracellular mechanisms. Indeed, Kingma et al (27,28), Denniss et al (29) and Werns et al (30) have documented significant reductions of infarct size in animal preparations of chronic coronary artery occlusion in the absence of restoration of blood flow.…”
Section: Myocardial Protectionmentioning
confidence: 99%
“…Animal studies (27)(28)(29)(30) have shown both antinecrosis and antiarrhythmic effects with a host of pharmacological agents that modulate different intraand extracellular mechanisms. Indeed, Kingma et al (27,28), Denniss et al (29) and Werns et al (30) have documented significant reductions of infarct size in animal preparations of chronic coronary artery occlusion in the absence of restoration of blood flow. Acute myocardial infarction significantly lowers vasoregulatory capacity, which probably contributes to reducing contractile dysfunction; however, postischemic deficits in cardiac contractile function (ie, myocardial stunning/hibernation) are dependent on the duration or severity of the ischemic insult and on the adequacy of return of blood flow to reversibly injured myocardium (31,32).…”
Section: Myocardial Protectionmentioning
confidence: 99%
“…Hence, considering a substantial (approx. 70%) inhibition of G-GCS by BSO treatment in vivo [3] and the decrement of about 27% of G-GCS activity observed in our severe ischemia-reperfusion model, it may be calculated that such a decrement could have conditioned a 15% decline in heart GSH content. A similar G-GCSrelated decline, although relatively small, might not be insignificant for the myocardium subjected to ischemia-reperfusion and oxidative stress [1].…”
Section: Discussionmentioning
confidence: 68%
“…Thus, the impaired GSH enzymatic biosynthesis of the reperfused myocardium, which represents a previously unrecognized finding, may contribute to tissue GSH depression after severe ischemia. In this context, studies performed with the G-GCS inhibitor buthionine sulfoximine (BSO) have shown that GSH concentrations are 40% lower in the perfused hearts of BSO-treated animals than in those of controls after ischemia-reperfusion [3]. Hence, considering a substantial (approx.…”
Section: Discussionmentioning
confidence: 99%
“…The assay was done in triplicate and IC50 values were calculated from the percentage inhibition (Werns et al, 1991).…”
Section: Analysis Using Autodock Toolsmentioning
confidence: 99%